Ice-induced vibrations of vertically sided offshore structures - Hendrikse, H. (author) (2017)
Offshore developments in ice-covered waters, such as the Arctic Ocean or Baltic Sea, have received increasing attention from the petroleum and wind power industries over the past decade. Sustainable developments in such waters can contribute to a balanced energy future provided that the deployed offshore structures are designed to be safe. The potential development of ice-induced vibrations has to be considered in the design of bottom founded offshore structures with a vertically sided waterline cross-section subject to ice. These vibrations, originating from dynamic interaction between the ice and structure, can result in high global peak loads and significantly contribute to the fatigue of structures. A governing theory which can explain the development of ice-induced vibrations has not yet been defined, despite several decades of research. As a consequence the tools required for detailed design of structures subject to ice-induced vibrations are not yet available. The main objective of this study is to define a physical mechanism which can explain the development of ice-induced vibrations and is consistent with existing experimental and full-scale observations. A literature study and new experiments in the large ice-basin at HSVA in Hamburg have resulted in the identification of key features of the interaction process. A new theory has been proposed, namely that the variations in the contact area between the intact ice and structure govern ice-induced vibrations. These variations result from the velocity dependent deformation and failure behaviour of the ice. Based on the theory a phenomenological model for the prediction of ice-induced vibrations has been developed of which the predictions have been shown to be consistent with experimental observations. Additionally, the limiting effect of ice buckling on ice-induced vibrations has been studied and practical application of the model illustrated on the basis of simulation examples. Applied Mechanics